Comparative studies of novel tri-state DC-DC converter - Yeo, Kenneth Keng Kwee. (2010)
This report describes the design, implementation and control of a tri-state DC-DC boost converter with fast dynamics. The boost converter converts a lower input DC voltage to a higher DC output voltage which is selectable by the user. In a conventional DC-DC boost converter, a change of load usually results in the time for the charging state to rise while reducing the time for the discharging state, resulting in a slower response. The fast dynamics results of the tri-state converter is the existence of the third free-wheeling state where increase in the charging cycle reduces the free-wheeling cycle time, leaving the discharging cycle unchanged. This increase in charging state does not affect the discharging state and this leads to a faster response. The feedback controllers implemented are three adaptive controllers with different structures. Experimental results of the tri-state boost converter are provided to illustrate the dynamic performances of these controllers under different operating conditions. The controllers are also compared with respect to their design and closed-loop performances.